Implementación de un programa nacional de actividades espacial del proyecto JICAAT, Perú, 2023-2032 - Huayanay Villar, José Luis (2024)
The objective of this work is to propose the implementation of a national program of space activities of the International Conference on Advanced Sciences Astrodynamics and Remote Sensing (JICAAT) project, directed by the Aerospace Research group of the company Villa Automation EIRL (V.A.), analyzing its problems in the recent past and list some proposed solutions to be implemented during the coming decades. The Research group proposes to develop Projects such as Satellite JICAAT, Launchers JICAAT, Nano robots and others. This initiative brings together several institutions interested in the development of Aerospace technologies, with the aim of developing prototypes and technologies for environmental studies, space debris mitigation, climate change and promoting research. The need for a rapprochement with society, to emphasize the importance of space activities, the International Conference on Advanced Astrodynamics and Remote Sensing Sciences was created in 2021, which are organized every year with topics that cover Mathematics, Physics, Statistics, Space Physics, Astrodynamics, Engineering, space technology engineering and remote sensing.